Development of Vehicle On-board Communication System for Harsh Environment - Aradi, Sz.; Bécsi, T.; Gáspár, P. (Acta Technica Jaurinensis, 2013)
Utilizing the already installed train interconnection cables as the physical layer of an extended intra-train communication could be a cost-effective solution. However these interconnection solutions are not optimal for the standardized digital data transfer solutions. The paper gives a brief summary of the theoretical aspects of data transmission, and experimental test results of the digital data transfer using non-standard physical layers.